Is Laparoscopic Technique Suitable for Initial Experience in Live Donor Nephrectomy Results of The First 51 Cases. Issue 6 (2021) - Akin, Emrah; Altintoprak, Fatih; Firat, Necattin; Dheir, Hamad; Celebi, Fehmi
No abstract available